Prevalence of risk factors for stuttering among boys: analytical cross-sectional study - Oliveira, Cristiane Moço Canhetti; Nogueira, Paula Roberta (São Paulo Medical Journal, 2014)
CONTEXT AND OBJECTIVE: There have been few studies on the risk factors for subgroups of stuttering. The aim of this study was to characterize the risk factors for developmental familial stuttering among boys who stutter and who do not stutter, such as disfluency types, associated quality and communication factors, emotional and physical stress, familial attitudes and personal reactions. DESIGN AND SETTING: Analytical cross-sectional study with a control group, performed at the Fluency Studies Laboratory of the Department of Speech and Hearing Disorders of a public university. METHODS: The parents of 40 age-matched stuttering and non-stuttering boys took part in this study. The participants were divided into two groups: stuttering children (SC) and non-stuttering children (NSC), with ages between 6 years 0 months and 11 years 11 months. Initially, all of the participants underwent a fluency assessment and then data were gathered using the Protocol for the Risk of Developmental Stuttering. RESULTS: There were no differences in the physical stress distribution factors and personal reactions between the groups. Inappropriate familial attitudes were presented by 95% of the SC and 30% of the NSC. Four risk factors analyzed were not shown by the NSC, namely stuttering-like disfluency, quality factors, physical stress and emotional stresses. CONCLUSIONS: The findings suggest that the presence of stuttering-like disfluency, associated quality and communication factors, emotional stress and inappropriate family attitudes are important risk factors for familial developmental stuttering among boys.